2019
DOI: 10.1080/09064710.2019.1596301
|View full text |Cite
|
Sign up to set email alerts
|

Repellency of insecticides and the effect of thiacloprid on bumble bee colony development in red clover (Trifolium pratense L.) seed crops

Abstract: The study intended to compare repellency of three insecticides on bumble bees and honey bees in Norwegian red clover (Trifolium pratense L.) seed crops, and to examine effects of thiacloprid on bumble bee colony development in the field. The repellency study was carried out in a large-scale field trial in SE Norway in 2013. On average for observations during the first week after spraying, 17 and 40 % less honey bees (P=0.03) and 26 and 20 % less bumble bees (P=0.36) were observed on plots sprayed with the pyre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 33 publications
0
13
0
Order By: Relevance
“…This finding suggests that bumble bees are unable to detect neonicotinoids in their food source, and do not interpret them as sweet. This information helps explain why several studies have determined that bumble bees do not avoid neonicotinoids when present in a food source (Gels et al 2002;Larson et al 2013;Havstad et al 2019). When these findings are taken together, there is evidence that bumble bees may face some of the same cellular-level impacts as a result of neonicotinoid exposure as honey bees.…”
Section: Cellular Responsesmentioning
confidence: 84%
See 2 more Smart Citations
“…This finding suggests that bumble bees are unable to detect neonicotinoids in their food source, and do not interpret them as sweet. This information helps explain why several studies have determined that bumble bees do not avoid neonicotinoids when present in a food source (Gels et al 2002;Larson et al 2013;Havstad et al 2019). When these findings are taken together, there is evidence that bumble bees may face some of the same cellular-level impacts as a result of neonicotinoid exposure as honey bees.…”
Section: Cellular Responsesmentioning
confidence: 84%
“…This finding suggests that bumble bees are unable to detect neonicotinoids in their food source, and do not interpret them as sweet. This information helps explain why several studies have determined that bumble bees do not avoid neonicotinoids when present in a food source (Gels et al 2002; Larson et al 2013; Havstad et al 2019).…”
Section: First Section Of Aopmentioning
confidence: 91%
See 1 more Smart Citation
“…Dead bees with a high internal concentration of thiacloprid were found in an overnight spray culture with 35% flowering. This shows that thiacloprid is not safe for bees if sprayed after anthesis and that spraying should be performed in the budding phase to reduce nectar and pollen contamination (Havstada et al, 2019). Despite the small number of articles published regarding thiacloprid toxicity in bees, it can be observed that this insecticide alters several characteristics of bees.…”
Section: Thiacloprid and Acetamipridmentioning
confidence: 99%
“…Therefore, bees need to be protected from exposure to neonicotinoids. Many studies investigated survival after insecticide treatment targeting the cholinergic system [35][36][37][38][39][40][41][42], and numerous studies have examined their effect on brood development by registering colony constitutions of honeybees (e.g., [43][44][45]) or bumblebees (e.g., [46][47][48]). Furthermore, sub-lethal neonicotinoid effects on adult honeybees comprise disturbances of navigation and orientation [49][50][51], walking behavior [52], learning and memory [53,54], foraging behavior [55], and nurse-larva-interactions [56].…”
Section: Introductionmentioning
confidence: 99%